THEORETICAL BASIS OF ARUZ WEIGHT - Goziyeva Feruza Otakoziyevna; Sultanov Sardorbek Nomonjon ogli; Turdimatov Iqrorjon Umarjon Ogli (International Engineering Journal For Research & Development, 2022)
The basis of classical poetry of the East is the trinity of sciences. These are the science of desire, the science of poetry, and the science of rhyme. In the history of our literature, these three sciences together are the criterion that defines the subtlety of classical poetry and the potential of the poet. Among them, the science of aruz is relatively complex, and not knowing it well makes it difficult to understand the essence of artistic creations created in classical genres. Therefore, this article is devoted to the analysis of the rules of application weight. The teaching of the theory of aruz is carried out through the work of classical artists, in particular, Alisher Navoi, who is the pinnacle of Uzbek poetry.